Leaf anatomical and molecular studies in Bulbophyllum section Micranthae (Orchidaceae) and their implications for systematics - Smidt, Eric de Camargo; Gallo, Leandro William [UNESP]; Scatena, Vera Lúcia [UNESP] (Springer Nature, 2013)
Bulbophyllum section Micranthae comprises 12 species of rupicolous or epiphytic orchids occurring in forests or in open rocky fields in Cerrado/Atlantic Forest ecotones throughout South America. We examined the leaf anatomy of 14 species and compared them with molecular data (nrITS) in phylogenetic analyses. The leaves of Bulbophyllum section Micranthae are characterised by uniseriate epidermis, with periclinal external cell wall thicker than the internal, presence of epicuticular wax, stomata present only on the abaxial surface with suprastomatic chambers, and collateral vascular bundles associated with sclerenchyma fibres. Some of these characters are shared with other rupicolous Orchidaceae species, demonstrating adaptive convergence in xeromorphic habitats. We found some anatomical characteristics with phylogenetic value. Bulbophyllum section Micranthae can be separated into two lineages: those with needle-like leaves, or flat leaves. The analyses show that anatomical characters as well as molecular data may contribute to the development of phylogenetic hypotheses. © 2013 Botanical Society of Sao Paulo.
Keywords: Anatomical characters; Character coding; Monocots; Phylogenetics